2021
DOI: 10.3389/fpsyg.2020.586633
|View full text |Cite
|
Sign up to set email alerts
|

A Bi-Dimensional Taxonomy of Social Responsivity in Middle Childhood: Prosociality and Reactive Aggression Predict Externalizing Behavior Over Time

Abstract: Developing social skills is essential to succeed in social relations. Two important social constructs in middle childhood, prosocial behavior and reactive aggression, are often regarded as separate behaviors with opposing developmental outcomes. However, there is increasing evidence for the co-occurrence of prosociality and aggression, as both might indicate responsivity to the social environment. Here, we tested whether a bi-dimensional taxonomy of prosociality and reactive aggression could predict internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Second, since participants were instructed to always send a noise blast, it is difficult to discover whether some children would rather have refrained from aggression or would have acted prosocially when receiving positive feedback. Children who show both self-protective as well as prosocial behaviors were previously found to show decreased externalizing behaviors over time ( Dobbelaar et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, since participants were instructed to always send a noise blast, it is difficult to discover whether some children would rather have refrained from aggression or would have acted prosocially when receiving positive feedback. Children who show both self-protective as well as prosocial behaviors were previously found to show decreased externalizing behaviors over time ( Dobbelaar et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children may use a combination of prosocial and aggressive strategies to gain social status (Hartl et al, 2020;Hawley, 2003). These children might be especially responsive to their environment, thereby showing both prosocial and RELATIONS BETWEEN PROSOCIAL AND PROBLEM BEHAVIORS 13 self-protective aggressive behaviors, based on the social context (Crone et al, 2020;Dobbelaar et al, 2020). This effect was not observed in early childhood and these developmental differences might arise from developmental differences in social relations and peer status.…”
Section: Random Intercept Cross Lagged Panel Modelsmentioning
confidence: 99%
“…To experimentally examine retaliation, the SNAT paradigm allows individuals to blast a loud noise to their peer(s) following feedback. Prior research showed that individuals give the loudest noise blasts following negative feedback, less following neutral feedback and least following positive feedback (Achterberg et al, 2016(Achterberg et al, , 2017(Achterberg et al, , 2018(Achterberg et al, , 2020Dobbelaar et al, 2021Dobbelaar et al, , 2022Van de Groep et al, 2021;van de Groep et al, 2022a). In our prior research in which we studied how young adults with childhood-onset persistent antisocial behavior, childhood-onset desistant antisocial behavior and typically developing young adults regulated their aggressive behavior following social feedback (van de Groep et al, 2022a), we observed that young adults with a persistent developmental trajectory of antisocial behavior showed similar levels of noise blast aggression as the other two groups following negative feedback.…”
Section: Aggression (Regulation) In Response To Social Feedbackmentioning
confidence: 99%